Long term follow-up can differenciate two subtypes of late-life psychosis (Archives of Clinical Psychiatry, 2005)
There are few studies about late-onset schizophrenia (LOS). LOS is thought to be a heterogeneous pathology with a similar cognitive profile compared to adult schizophrenia and two types of evolution: one group with steady neuropsychological deficits and another group with progressive deficits. We report on two clinical cases evaluated with neuropsychological tests CAMCOG and MMSE, Hachinski's Ischemic Score, Pfeffer Functional Activities Questionnaire, PANSS and the Neuropsychiatric Inventory. The course of cognitive deficits and daily life activities were different, showing the need of prospective studies with neuropsychological approach to understand the clinical course and etiology of LOS.